Local structure investigation of (Co, Cu) co-doped ZnO nanocrystals and its correlation with magnetic properties. (March 2016) - Tiwari, N.; Doke, S.; Lohar, A.; Mahamuni, Shailaja; Kamal, C.; Chakrabarti, Aparna; Choudhary, R.J.; Mondal, P.; Jha, S.N.; Bhattacharyya, D.
Abstract: Pure, Co doped and (Co, Cu) co-doped ZnO nanocrystals have been prepared by wet chemical route at room temperature to investigate the effect of Cu doping in Co doped ZnO nanocrystals . The nanocrystals have initially been characterized by X-ray diffraction, FTIR, Raman, optical absorption and EPR spectroscopy and the results were corroborated with DFT based electronic structure calculations. Magnetic properties of the samples have been investigated by studying their magnetic hysteresis behavior and temperature dependence of susceptibilities. Finally the local structure at the host and dopant sites of the nanocrystals have been investigated by Zn, Co and Cu K edges EXAFS measurements with synchrotron radiation to explain their experimentally observed magnetic properties. Highlights: Pure, Co doped and (Co, Cu) co-doped ZnO nanocrystals have been prepared by wet chemical route. The nanocrystals have been characterized by XRD, TEM, FTIR, Raman, optical absorption, EPR, magnetic measurements and EXAFS. (2.5% Co, 2.5% Cu) co-doped sample shows weak FM behavior and its magnetisaion is less than that of the Co doped sample. EXAFS study clearly establishes that Cu is present as CuO in the samples which is detrimental to its magnetic properties.